Targeting Herpes Simplex Virus Glycoprotein D with Bispecific Antibodies: Expanding Therapeutic Horizons by Searching for Synergy - Doina Atanasiu; Wan Ting Saw; Harvey M. Friedman; Gary H. Cohen (Viruses, 2025)
Herpes simplex viruses (HSV-1 and HSV-2), which can be transmitted both orally and sexually, cause lifelong morbidity and in some cases, meningitis and encephalitis. While both the passive transfer of neutralizing antibodies and placental transfer of anti-HSV monoclonal antibodies (Mabs) have shown therapeutic promise in animal models, clinical trials have yet to identify approved immunotherapeutics for herpes infection. Here, we present strategies for the generation of recombinant bispecific antibodies (BsAbs) that target different domains of glycoprotein D (gD), crucial for HSV entry, that have the potential to outperform the effect of individual Mabs to curb herpes infection. Specifically, we selected three pairs of Mabs from our extensive panel for BsAb design and production based on their binding site and ability to block virus entry. Actual binding of BsAbs to gD and epitope availability on gD after BsAb binding were characterized using surface plasmon resonance (SPR) and inhibition by IgG Fab fragments generated from selected Mabs. While one BsAb exhibited an additive effect similar to that observed using a combination of the Mabs utilized for its generation, two showed antagonistic effects, suggesting that the simultaneous engagement of two epitopes or selective binding to one affected their activity against HSV. One BsAb (DL11/1D3) targeting the binding site for both nectin-1 and HVEM receptors demonstrated synergistic inhibitory activity against HSV, outperforming the effect of the individual antibodies. Recombinant DL11/1D3 antibody variants, in which the size of one or both paratopes was decreased to single chains (scFv-Fc), highlighted differences in potency depending on antibody size and format. We propose that BsAbs to individual glycoproteins offer a potential avenue for herpes therapeutics, but their design, mechanism of action, antibody format, and epitope engagement require careful consideration of structure for optimal efficacy.